1988
DOI: 10.1002/ecja.4410710401
|View full text |Cite
|
Sign up to set email alerts
|

Parallel queues with common service process and their input controls

Abstract: In the parallel queue with common service process, there are m independent arrival processes to m waiting spaces. When customers are waiting in all of the waiting areas, the server accepts a customer from each waiting space, and the service is made simultaneously to the m customers. This paper discusses the fundamental properties of such a system, presenting the approximate analysis, qualitative interpretations, and simulation. It has been well known that this kind of system is essentially unstable for any loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Sasieni (1961) also showed that if the arrival and service rates are independent of the queue length, then at least one of the buffers will be unstable and grow indefinitely as time evolves. Through simulation experiments, Fukuda et al (1988) numerically showed that this instability occurs independently of the load of the server. For a multiple input generalization of the GI /G/1 queue, Harrison (1973) proved that an equilibrium of the system never exists if the capacity is infinite.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Sasieni (1961) also showed that if the arrival and service rates are independent of the queue length, then at least one of the buffers will be unstable and grow indefinitely as time evolves. Through simulation experiments, Fukuda et al (1988) numerically showed that this instability occurs independently of the load of the server. For a multiple input generalization of the GI /G/1 queue, Harrison (1973) proved that an equilibrium of the system never exists if the capacity is infinite.…”
Section: Introductionmentioning
confidence: 95%
“…Hence, in order to avoid instability, one needs some mechanism of controlling the buffer contents in the system by limiting inputs. Simple control limit policies have been discussed in the previous literature (Duenyas and Hopp 1993;Foster 1959;Fukuda et al 1988;Keblis and Duenyas 1999). Kashyap (1966) assumed limited waiting spaces for both customers as a mechanism to limit the buffer capacity.…”
Section: Introductionmentioning
confidence: 97%